Asuransi Pertanian dalam Perspektif Undang-Undang No 19 Tahun 2013 Tentang Perlindungan dan Pemberdayaan Petani - Arifatul Uyun; Busriyanti Busriyanti (Sharia Faculty, Kiai Haji Achmad Siddiq State Islamic University of Jember, 2020)
Indonesia is an agricultural country that has a tropical climate, with two seasons. This condition makes the agricultural sector in Indonesia very dependent on natural conditions. As a measure to protect farmers, the government undertakes protection measures with agricultural insurance as a step towards shifting the risk of possible losses due to certain factors. Agricultural insurance which is regulated in Law No. 19 of 2013 concerning the protection and empowerment of farmers regulates rice farming insurance and cow/ buffalo business insurance. This research uses normative legal research. The purpose of this study is to examine the concept of the agreement as well as aspects of protection and empowerment for farmers according to Law No. 19 of 2013. Agricultural insurance is a government program regulated in Law No. 19 of 2013 concerning Protection and Empowerment of Farmers to protect farmers from losses caused by due to natural factors, in which there is also a big role for the community and the government in implementing agricultural insurance.